Causal relationship between 91 circulating inflammatory proteins and gynecological diseases: A two-sample bidirectional Mendelian randomization study - Wang, Jie-Lin; Zhang, Ping-An; Yuan, Jing; Huang, Xiang-Chun; Cheng, Jia-Chen; Bao, Hai-Juan; Li, Jing; Chen, Shuo (International journal of biological macromolecules, 2025)
Gynecological diseases pose major public health challenges due to their detrimental impact on women's quality of life and fertility. While growing evidence implicates inflammatory proteins in the pathogenesis of these conditions, their causal roles remain unclear. In this study, we conducted a bidirectional two-sample Mendelian randomization (TSMR) analysis to explore causal relationships between 91 circulating inflammatory proteins and 17 gynecological diseases in a discovery cohort. We identified nine protein–disease pairs with potential causal associations, three of which remained significant after Bonferroni correction, including IL-1α with increased risk of cervical cancer, MMP10 with reduced risk of endometrial cancer, and MCP-1 with increased susceptibility to ovarian benign neoplasms. A meta-analysis incorporating data from an independent replication cohort further suggested that IL-1α increases the risk of cervical cancer. To validate these findings, we performed transcriptomic analysis using the TCGA database and confirmed protein-level expression through Western blot analysis of clinical samples. Collectively, these results provide novel insights into the inflammatory mechanisms underlying gynecological diseases and underscore IL-1α as a promising causal biomarker and potential therapeutic target for cervical cancer. •First MR study on causal links between 91 inflammatory proteins and 17 gynecological disorders.•9 protein–disease pairs showed potential causal associations, with 3 remaining significant after Bonferroni correction.•IL-1α identified as a causal risk factor for cervical cancer, validated by meta-analysis, TCGA, and protein assays.•These findings provide new insights into inflammation-related mechanisms in gynecological diseases.